Double Colonization: A Postcolonial Feminist Study Of Sia Figiel’s Where We Once Belonged - Shene Mohammad Ahmed (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
The article deals with analyzing female characters in the WHERE WE ONCE BELONGED by Sia Figiel. The novel is important for students who study postcolonialism and feminism as it gives an insight for gender and race issues. The aim of this article is to show how females in a male-dominated societies are persecuted. Furthermore, females are regarded as inferior according to Edward Said’s theory of Orientalism. The Samoan culture was once colonized by the British. Therefore, the legacy of colonialism and its effects remains there, even after the national independence. It first gives some clarifications about the publishing of the novel and the writer. Then, it comes to the discussion about the colonialism in the novels with its connections to the main characters and how the colonizers were, and also how it affected their lives. In the next part, it explains double colonization. It talks about how almost all of the postcolonial writings were occupied by how women were muted. Then, it recalls how the female characters were suppressed and oppressed by the males and the English dominant power. It shows how they were double-colonized, not having even the freedom to show it.